Characterization of a Novel Insect-Induced Sesquiterpene Synthase GbTPS1 Based on the Transcriptome of Gossypium barbadense Feeding by Cotton Bollworm - Zhang, Hang; Liu, Enliang; Huang, Xinzheng; Kou, Junfeng; Teng, Dong; Lv, Beibei; Han, Xiaoqiang; Zhang, Yongjun (Frontiers in Plant Science, 2022)
When attacked by insect herbivores, plants initiate sophisticated defenses mediated by complex signaling networks and usually release a blend of functional volatiles such as terpenes against infestation. The extra-long staple cotton Gossypium barbadense cultivated worldwide as natural textile fiber crop is frequently exposed to a variety of herbivores, such as cotton bollworm Helicoverpa armigera. However, little is known about insect-induced transcriptional changes and molecular mechanisms underlying subsequent defense responses in G. barbadense. In the current study, transcriptome changes in G. barbadense infested with chewing H. armigera larvae were investigated, and we identified 5,629 differentially expressed genes (DEGs) in the infested cotton leaves compared with non-infested controls. H. armigera feeding triggered complex signaling networks in which almost all (88 out of 90) DEGs associated with the jasmonic acid (JA) pathway were upregulated, highlighting a central role for JA in the defense responses of G. barbadense against target insects. All DEGs involved in growth-related photosynthesis were downregulated, whereas most DEGs associated with defense-related transcript factors and volatile secondary metabolism were upregulated. It was noteworthy that a terpene synthase gene in the transcriptome data, GbTPS1, was strongly expressed in H. armigera-infested G. barbadense leaves. The up-regulation of GbTPS1 in qPCR analysis also suggested an important role for GbTPS1 in herbivore-induced cotton defense. In vitro assays showed that recombinant GbTPS1 catalyzed farnesyl pyrophosphate and neryl diphosphate to produce three sesquiterpenes (selinene, α-gurjunene and β-elemene) and one monoterpene (limonene), respectively. Moreover, these catalytic products of GbTPS1 were significantly elevated in G. barbadense leaves after H. armigera infestation, and elemene and limonene had repellent effects on H. armigera larvae in a dual-choice bioassay and increased larval mortality in a no-choice bioassay. These findings provide a valuable insight into understanding the transcriptional changes reprograming herbivore-induced sesquiterpene biosynthesis in G. barbadense infested by H. armigera, which help elucidate the molecular mechanisms underlying plant defense against insect pests.